Low molecular weight hyaluronan, via AP-1 and NF-κB signalling, induces IL-8 in transformed bronchial epithelial cells (Swiss Medical Weekly, 2011)
QUESTIONS UNDER STUDY: New evidence demonstrated that high tidal volume mechanical ventilation results in substantial bronchial airway mechanical strain. In addition, high tidal volume mechanical ventilation has been shown to increase IL-8 production in a mechanism mediated, at least in part, by low molecular weight hyaluronan (LWM-HA). In the present study, it was investigated whether LMW-HA synthesised in the lung, in response to cyclic stretch, increased IL-8 production in the bronchial epithelium. METHODS: This question was approached by stimulating a transformed human bronchial epithelial cell line with LMW-HA isolated from stretched human lung fibroblasts and probed for the activation of extracellular signal-regulated kinase pathways. RESULTS: LMW-HA increased IL-8 secretion in transformed bronchial epithelial cells. Additionally, LMW-HA augmented the levels of phospho c-Jun NH2-terminal kinase (JNK) and phospho extracellular signal-regulated kinase 1/2 (ERK1/2), and also mobilised nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) from the cytoplasm to the nucleus. The inhibition of JNK, ERK1/2 and NF-κB blocked IL-8 secretion in response to LMW-HA. CONCLUSION: The data suggest that LMW-HA produced by lung fibroblasts in response to cyclic stretch increases the secretion of IL-8 in transformed bronchial epithelial cells via AP-1 and NF-κB signalling pathways. These findings support the hypothesis that LMW-HA plays an active role in acute lung inflammation triggered by mechanical strain.